PERAN MEDIA SOSIAL INSTAGRAM DALAM INTERAKSI SOSIAL ANTAR KARYAWAN BANK BTPN BUMIAYU - Dewi Astuti; Bekti Istiyanto (Fakultas Dakwah dan Komunikasi, 2019)
Instagram is a social media that is already familiar to the public. Information is quickly and easily accepted by all Instagram users. No wonder Instagram became one of the social media that is very much loved by all people. Instagram is very effective and efficient in finding information and news that is happening in the community. But behind the effectiveness and efficiency, there are positive values and negative values that arise in it, because Instagram has a certain impact that can occur in the community according to one's own perspective. Instagram social media plays a very strong role in social changes, both changes in behavior, mindset and lifestyle. This study uses a qualitative descriptive method to determine the role of Instagram social media among employees of Bank BTPN Bumiayu, with data analysis techniques using observation and interviews. The results show that Instgram is a favorite media for employees of Bank BTPN Bumiayu. Many advantages, uniqueness and satisfaction they get through their Instagram account. There are also many positive and negative sides that influence social interaction between employees. However, employees are able to be wise in understanding and using Instagram social media accounts.